2018
DOI: 10.7759/cureus.2282
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Healthcare Received at an Interprofessional Student-run Free Clinic: Invested in Training the Next Generation of Healthcare Professionals

Abstract: Most medical schools in the United States have an associated student-run free clinic (SRFC) providing medical care to the underserved population around the campus. SRFCs provide students with opportunities to practice history-taking and diagnosis skills. There have been a few studies that have evaluated patient satisfaction within SRFCs; however, these studies report limited aspects of care within these clinics. This study hopes to determine the levels of satisfaction with clinical staff and operations and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 4 publications
(4 reference statements)
2
17
0
Order By: Relevance
“…Consistent with our findings at SHAWCO, several studies have found high patient satisfaction ratings of student-run free clinics [6,[9][10][11]. Interestingly, SHAWCO patients rated medical students higher than physicians on listening to their concerns.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with our findings at SHAWCO, several studies have found high patient satisfaction ratings of student-run free clinics [6,[9][10][11]. Interestingly, SHAWCO patients rated medical students higher than physicians on listening to their concerns.…”
Section: Discussionsupporting
confidence: 90%
“…This highlights a niche role for students on a patient care team. In a study conducted at the University of Central Florida KNIGHTS clinic, Lu et al found that patients identified free/affordable medical care, primary/specialty care, and the team approach as the greatest strengths of SRFCs [10]. Based on our results, the presence of students at SRFCs may enhance patient care by adding a layer to the "team approach."…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Volunteer students serve the community by providing care to vulnerable and marginalized populations that may not have access to healthcare otherwise. Patients seen at student-run clinics report overall positive experiences and high satisfaction (Ellett et al 2010;Mischell et al 2017;Lu et al 2018). The positive experiences of the students and patients may also have long-term benefits.…”
Section: Enlightened Self-interest In Altruism (Esia)mentioning
confidence: 99%
“…This form of evaluation however can only capture the participant's reaction to the service and does not capture higher level evaluation, including the ability of the intervention to facilitate learning and behaviour change [8]. Accordingly, the results from patient satisfaction questionnaires, often suggest that overall patients are satisfied with student services [9][10][11][12][13][14] providing the lowest level of evaluation according to the Kirkpatrick model [8]. Satisfaction may also be influenced by personal factors such as the patient's ability to access healthcare [15] or communication and interpersonal skills of the students.…”
Section: Introductionmentioning
confidence: 99%